2018
DOI: 10.1016/j.ajem.2017.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Utility of common bile duct measurement in ED point of care ultrasound: A prospective study

Abstract: Of patients diagnosed with biliary pathology, none had isolated CBD dilatation. In the absence of abnormal laboratory values and GWT, PCF or SMS on POCUS, obtaining a CBD measurement is unlikely to contribute to the evaluation of this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Bernard et al found that a multimodal educational approach significantly improved the levels of confidence of medical students in scanning the head and neck regions, and that instructor demonstrations were rated as the most crucial component of the program [9]. Recently, point-of-care ultrasound (POCUS) has been increasingly used at patients’ bedside for diagnostic and therapeutic purposes [10, 11] . POCUS also enables emergency or primary care physicians to quickly recognize musculoskeletal and soft tissue disorders and to provide better and safer cares [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bernard et al found that a multimodal educational approach significantly improved the levels of confidence of medical students in scanning the head and neck regions, and that instructor demonstrations were rated as the most crucial component of the program [9]. Recently, point-of-care ultrasound (POCUS) has been increasingly used at patients’ bedside for diagnostic and therapeutic purposes [10, 11] . POCUS also enables emergency or primary care physicians to quickly recognize musculoskeletal and soft tissue disorders and to provide better and safer cares [12].…”
Section: Introductionmentioning
confidence: 99%
“…One study performed PoCUS on patients presenting with non-traumatic epigastric pain, and found a cholelithiasis prevalence of 39% in this population, even though the treating EP did not initially consider the need for biliary ultrasound in 85% of these cases [132]. A USA study found that the presence of a dilated common bile duct on EP-performed PoCUS, in the absence of laboratory findings or signs of cholecystitis on ultrasound, was unlikely to be a good indicator for complicated biliary pathology (sensitivity 23.7% and specificity 77.9%) [133].…”
Section: Resultsmentioning
confidence: 99%
“…35 The Use of Bedside Ultrasound for Gallstone Disease Care within a Community-based Emergency Department: A Confirmation Bias Despite the literature demonstrating the utility of a Bedside US, the use of this modality remains restricted. 44 The arguments against Bedside US use (e g., importance of obtaining an isolated common bile duct dilation measurement, inferiority to an accredited radiography US or limitation with non-fasting patients) have been disproven. 44,45 However, in our study, only 7.2% of our patients received a Bedside US.…”
Section: Discussionmentioning
confidence: 99%